Immune system and intestinal microbiota determine efficacy of androgen deprivation therapy against prostate cancer. Issue 3 (16th March 2022) - Terrisse, Safae; Goubet, Anne-Gaelle; Ueda, Kousuke; Thomas, Andrew Maltez; Quiniou, Valentin; Thelemaque, Cassandra; Dunsmore, Garett; Clave, Emmanuel; Gamat-Huber, Melissa; Yonekura, Satoru; Ferrere, Gladys; Rauber, Conrad; et al.
Abstract : Background: Prostate cancer (PC) responds to androgen deprivation therapy (ADT) usually in a transient fashion, progressing from hormone-sensitive PC (HSPC) to castration-resistant PC (CRPC). We investigated a mouse model of PC as well as specimens from PC patients to unravel an unsuspected contribution of thymus-derived T lymphocytes and the intestinal microbiota in the efficacy of ADT. Methods: Preclinical experiments were performed in PC-bearing mice, immunocompetent or immunodeficient. In parallel, we prospectively included 65 HSPC and CRPC patients (Oncobiotic trial) to analyze their feces and blood specimens. Results: In PC-bearing mice, ADT increased thymic cellularity and output. PC implanted in T lymphocyte-depleted or athymic mice responded less efficiently to ADT than in immunocompetent mice. Moreover, depletion of the intestinal microbiota by oral antibiotics reduced the efficacy of ADT. PC reduced the relative abundance of Akkermansia muciniphila in the gut, and this effect was reversed by ADT. Moreover, cohousing of PC-bearing mice with tumor-free mice or oral gavage with Akkermansia improved the efficacy of ADT. This appears to be applicable to PC patients because long-term ADT resulted in an increase of thymic output, as demonstrated by an increase in circulating recent thymic emigrant cells (sjTRECs). Moreover, as compared with HSPC controls, CRPC patients demonstrated a shift in their intestinal microbiota that significantly correlated with sjTRECs. While feces from healthy volunteers restored ADT efficacy, feces from PC patients failed to do so. Conclusions: These findings suggest the potential clinical utility of reversing intestinal dysbiosis and repairing acquired immune defects in PC patients.